Prevalence of feline hyperthyroidism in Greece - Kokkinaki, KCG; Xenoulis, PG; Steiner, JM; Suchodolski, JS; Mylonakis, ME; Saridomichelakis, MN (Journal of the Hellenic Veterinary Medical Society, 2025)
Hyperthyroidism is the most common endocrine disease of cats and usually occurs in middle-aged to older animals. The primary aim of this study was to determine the prevalence of feline hyperthyroidism in Greece, and a secondary aim was to compare the clinical signs, haematological and serum biochemical findings between hyperthyroid and non-hyperthyroid cats. A total of 80 cats, six years of age or older, were prospectively enrolled. The diagnosis of hyperthyroidism was based on serum concentrations of total thyroxine (measured by a solid-phase chemiluminescent competitive assay) and free thyroxin (measured by an equilibrium dialysis radioimmunoassay). Hyperthyroidism was diagnosed in 4/80 (5%) of the cats. Clinical and laboratory findings that were significantly more common in hyperthyroid compared to the non-hyperthyroid cats included a palpable thyroid nodule, depression-lethargy, dyspnoea, and decreased blood urea nitrogen concentration. Feline hyperthyroidism appears to be relatively common in Greece and routine measurement of thyroid hormone concentration should be considered in all middle-aged and older cats.